The Bahamas : the case for public sector modernization (CARICAD [St. Michael]BB, 2006)
Presents an overview of Bahamian governance, the economy and domestic and international challenges. Focuses on public sector reform, strategic public sector human resource management initiatives and public sector reform initiatives. Concludes with the lessons learnt.
Keywords: PUBLIC SECTOR